2022
DOI: 10.1186/s12910-022-00751-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about withholding or withdrawing life-prolonging treatment, euthanasia, assisted suicide, and physician assisted suicide: a cross-sectional survey among the general public in Croatia

Abstract: Background There has been no in-depth research of public attitudes on withholding or withdrawing life-prolonging treatment, euthanasia, assisted suicide and physician assisted suicide in Croatia. The aim of this study was to examine these attitudes and their correlation with sociodemographic characteristics, religion, political orientation, tolerance of personal choice, trust in physicians, health status, experiences with death and caring for the seriously ill, and attitudes towards death and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Below we summarize the main tendencies in the responses. However, one of the most striking findings is the large variation in the answers, as also found in other studies [13][14][15][16][17]. We will return to this finding in the discussion of implications for practice.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Below we summarize the main tendencies in the responses. However, one of the most striking findings is the large variation in the answers, as also found in other studies [13][14][15][16][17]. We will return to this finding in the discussion of implications for practice.…”
Section: Discussionsupporting
confidence: 63%
“…In a Dutch study, more than half of respondents would refuse life-prolonging treatment for themselves in case of advanced cancer or advanced dementia [13]. Several studies, however, show that respondents are sensitive to how scenarios and decisions are described, and that there is significant variation in attitudes with a minority apparently not being accepting of NTDs [13][14][15][16][17].…”
Section: European Citizens' Attitudes To Non-treatment Decisionsmentioning
confidence: 99%
“…Studies in diverse populations by seeking research across populations with different ages, rural and urban settings, and countries beyond the United States were selected. 10,[16][17][18][19][20][21]…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies in other countries also indicate that the level of acceptance for this type of practice is still not high. For example, studies conducted on a random sample of adult citizens in the Republic of Croatia showed a low level of acceptance for withholding or withdrawing life-prolonging treatment, euthanasia, assisted suicide and physician-assisted suicide [26]. Results from a poll conducted in the UK by the Royal College of Nursing indicated that 40% of nurses were against assisted suicide, while 49% of nurses supported this action [27].…”
Section: Introductionmentioning
confidence: 99%